2012
DOI: 10.1093/nar/gks530
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of rRNA processing and translation in mammalian cells using a synthetic 18S rRNA expression system

Abstract: Analysis of processing, assembly, and function of higher eukaryotic ribosomal RNA (rRNA) has been hindered by the lack of an expression system that enables rRNA to be modified and then examined functionally. Given the potential usefulness of such a system, we have developed one for mammalian 18S rRNA. We inserted a sequence tag into expansion segment 3 of mouse 18S rRNA to monitor expression and cleavage by hybridization. Mutations were identified that confer resistance to pactamycin, allowing functional analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…We previously demonstrated that recombinant 18S rRNA expressed from a plasmid in mouse N2a cells was correctly processed and incorporated into fully functional ribosomal subunits capable of mediating global protein synthesis as well as translation driven by poliovirus and encephalomyocarditis virus IRESs (29). As an initial step toward a functional analysis of the hypothesized basepairing interaction between HCV IRES and 18S rRNA, we examined whether our synthetic 18S rRNA expression system supports HCV IRES-dependent translation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously demonstrated that recombinant 18S rRNA expressed from a plasmid in mouse N2a cells was correctly processed and incorporated into fully functional ribosomal subunits capable of mediating global protein synthesis as well as translation driven by poliovirus and encephalomyocarditis virus IRESs (29). As an initial step toward a functional analysis of the hypothesized basepairing interaction between HCV IRES and 18S rRNA, we examined whether our synthetic 18S rRNA expression system supports HCV IRES-dependent translation.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were transfected with a plasmid that expresses mouse 18S rRNA with a G963A mutation (mouse numbering) that confers resistance to pactamycin ( Fig. S1A) (29). After 48 h, cells were subsequently transfected with a series of dicistronic reporter constructs, each encoding Renilla luciferase (Rluc) and Photinus luciferase (Pluc) from the first and second cistron, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations